Neural network based feedback linearization control of a servo-hydraulic vehicle suspension system - Pedro, Jimoh Olarewaju; Dahunsi, Olurotimi Akintunde (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the design of a neural network based feedback linearization (NNFBL) controller for a two degree- offreedom (DOF), quarter-car, servo-hydraulic vehicle suspension system. The main objective of the direct adaptive NNFBL controller is to improve the system?s ride comfort and handling quality. A feedforward, multi-layer perceptron (MLP) neural network (NN) model that is well suited for control by discrete input-output linearization (NNIOL) is developed using input-output data sets obtained from mathematical model simulation
Keywords: neural networks; direct adaptive control; feedback linearization control; PID control; ride comfort; suspension system; servo-hydraulics